APPLICATION OF THE WAVE METHOD CONTINUATION OF POTENTIAL FIELDS IN THE LOWER HALF AREA TO STUDY THE DEEP STRUCTURE OF THE EARTH AND SEARCH FOR MINERAL DEPOSITS - Bankovskyi М.; Geikhman А.; Potapchuk І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper considers a methodology for studying the deep structure of the Earth and searching for mineral deposits, primarily oil and gas, based on wave (holographic) transformation of the data of gravitational, magnetic and geothermal fields into a spatial 3D model of these fields in combination with geological and seismic studies. The paper presents the physical principles on which the theory of the method is based and describes the methodology and software package that implements the method. The examples of the application of the holographic method for studying the deep structure of the Earth, tracing faults and searching for minerals the prospects for applying this approach are shown. The practical significance of the work lies in the fact that the proposed method, if desired, can be successfully used both for studying the deep structure of the Earth and for searching for various mineral deposits.